EDUCATOR AND HIS ROLE IN SOCIETY (International journal of artificial intelligence, 2025)
In this article, the teacher's professional skills and purpose, task of competence, preschool educational institution educator's competence, educator's pedagogical skills,the image of a modern teacher, the teacher is creative in his pedagogical activity approach, organization of classes in preschool educational institutions ways, the educator's innovative activity, the preschool education system technologyization, preschool education in developed countries includes the peculiarities of the system.